The growth of SMEs amid the COVID-19 pandemic in Ghana - Aidoo, Samuel (Goodwood Publishing, 2022)
Purpose: This study aimed to determine how Ghana's small and medium-sized businesses (SMEs) performed in terms of growth during the COVID-19 pandemic. Research Methodology: This study adopted a quantitative research method, alongside descriptive and explanatory research designs. Primary data were gathered from 400 SMEs in the general trading and manufacturing industries. Descriptive statistical analyses and Pearson multiple regression analyses were performed using the Statistical Package for Social Sciences (SPSvs.26) and XL Stats. Results: The most critical challenges faced by SMEs during the COVID-19 pandemic include a decrease in sales revenue, followed by the inability of SMEs to pay staff, retrenchment of workers, shortages of raw materials, halted operations, difficulty in supplying goods and services, inability to repay loans, insufficient capital, cash flow shortages, accounting deficiencies, and the least critical challenge associated with a lack of advanced technology. The next major finding was that lockdowns, movement restrictions, social distancing, and market closures had significant negative effects on SMEs’ growth. Limitations: Varied responses from SMEs in other regions and industries in the country were not gathered. Furthermore, the research instrument ignored the direct views of SME owners and managers regarding the challenges they encountered. Contributions: The findings are important for entrepreneurs and managers of SMEs, financial institutions, government, and other stakeholders for decision-making purposes. Novelty: The effect of the pandemic has mostly been linked to financial performance. No study in the Ghanaian context has investigated the effect of the COVID-19 pandemic on the growth of trading and manufacturing SMEs.